Search for techniparticles in e+jets events at D0 - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2007)
We search for the technicolor process pp̄→ρT/ ωT→WπT in events containing one electron and two jets, in data corresponding to an integrated luminosity of 390pb-1, recorded by the D0 experiment at the Fermilab Tevatron. Technicolor predicts that technipions πT decay dominantly into bb̄, bc̄, or b̄c, depending on their charge. In these events b and c quarks are identified by their secondary decay vertices within jets. Two analysis methods based on topological variables are presented. Since no excess above the standard model prediction was found, the result is presented as an exclusion in the πT vs ρT mass plane for a given set of model parameters. © 2007 The American Physical Society.